Fundamental factors affecting income inequality among provinces of Iran - Mohammad Bager Beheshti; parviz mohamadzade; khalil ghasemloo (پژوهش‌های برنامه و توسعه)
.Abstract:One of the important issues in regional economics is how the resources and facilities of the country are distributed in the spatial and geographic dimension, so that it does lead to regional balances. One of the indicators of imbalance between regions is the inequality of per capita income. In this regard, identification of factors affecting income inequalities among regions will play an important role in policy making for regional equilibriumThe purpose of this study is to identify the causes of per capita inequality among the provinces of Iran during the period of 2000-2014. To achieve the research goal, the role of various economic factors in increasing income inequality among the provinces with using the fixed effects method of Panel data regression model was studied.The estimated regression model showed that the impact of the relative advantage indexes in industrial goods, the gap in the government spending in the provinces, the concentration of industrial activities, the difference in human capital and relative advantage in the tourism industry on income inequality were positive.